Assessing the Role of Emergency Physicians in Medical Clearance: Predictors of Diagnosing Psychiatric Illness in the Emergency Department – A Retrospective Cross-sectional Study - Ibrahim Khamis Abdullah Almamari; Darpanarayan Hazra; Awatif K. Alsarrai Al-Alawi (Current Medical Issues)
Background: Medical clearance for patients presenting with psychiatric-like illnesses has been a topic of debate for years. This study aimed to determine the predictors of diagnosing psychiatric illness in the emergency department (ED). Methods: The study included patients aged ≥13 years presenting to the adult ED with psychiatric-like illness over 1 year (January 01, 2019–December 31, 2019). Medical charts were reviewed, and multiple variables were coded and analyzed. Results: Our study included 361 patients, constituting 0.89% of the total ED visits. The majority (335 patients, 92.8%) were diagnosed with primary psychiatric illnesses, while 26 patients (7.2%) had underlying medical conditions contributing to their symptoms. Bivariate and multivariate logistic regression analysis identified the predictors for initial psychiatric diagnoses, including abnormal behavior (odd’s ratio [OR]: 8.29; 95% confidence interval [CI]: 2.04–33.65; P < 0.01) and substance abuse (adjusted OR: 17.27; 95% CI: 3.88–76.88; P < 0.01). Notable findings involved family history or previous psychiatric illness (OR: 2.32; 95% CI: 0.59–6.09; P < 0.01), absence of medical comorbidities (adjusted OR: 2.47; 95% CI: 1.05–5.86; P < 0.01), and no new medication initiation before illness (OR: 6.43; 95% CI: 1.52–27.18; P < 0.01), normal sensorium (adjusted OR: 2.84; 95% CI: 0.81–10.00; P < 0.01) and intact orientation (adjusted OR: 6.73; 95% CI: 1.24–36.42; P < 0.01) demonstrated statistically significant predictors of an initial psychiatric diagnosis in the ED. Conclusion: Significant predictors of initial psychiatric illness included abnormal behavior, substance abuse, family psychiatric history, absence of major medical conditions, no recent medication changes before illness onset, normal sensorium and orientation, and normal laboratory markers at presentation.